Review: Emulsification properties of soy bean protein - WENPU CHEN; XIANG LI; MD. RAMIM TANVER RAHMAN; NABIL QAID M. AL-HAJJ; KAMALESH CHANDRA DEY; SALEH MUHAMMED RAQIB (Smujo International, 2014)
Chen W, Li X, Rahman MRT, Al-Hajj NQM, Dey KC, Raqib SM. 2014. Emulsification properties of soy bean protein. Nusantara Bioscience 6: 196-202. Emulsion stability and emulsifying ability are two important factors in food industry. Soy protein has the great of interest because of its amphilic structure. Î²-Conglycinnin and glycinin are main components in soy protein which can be used as emulsifiers in food processing. However, due to its size and molecular weight, the emulsifying ability of soy protein is limited. By chemical, physical and enzymatic modification, the emulsifying ability of soy protein can be improved. The addition of polysaccharides in emulsion is common. The interaction of polysaccharides and proteins are being discussed in this review. In some complex food emulsion, the function of soy protein molecules and emulsifier at the interface need to be investigated in the future study.